The Use of Antipsychotic Drugs for Treating Behavioral Symptoms in Alzheimer’s Disease - Calsolaro, Valeria; Antognoli, Rachele; Okoye, Chukwuma; Monzani, Fabio (Frontiers in Pharmacology, 2019)
According to the World Alzheimer’s report, dementia was estimated to affect 50 million worldwide in 2018, number expected to increase to more than 150 million within 30 years. Alzheimer’s disease is the most common type of dementia, accounting on its own for 2/3 of all dementia cases. The initial signs and symptoms of Alzheimer’s disease relate to progressive cognitive decline, inexorably progressing until the loss of independence. Neuropsychiatric and behavioral symptoms may occur during the progression of the disease; around 20% of patients without any behavioral symptoms at the diagnosis will experience some of them within 2 years. Consequences are early institutionalization, lower quality of life, of both patients and carers, and more severe cognitive impairment. Treatment options for behavioral symptoms include pharmacological and non-pharmacological approaches. The latter are usually preferred, since antipsychotic therapy is not free from several, and often serious, adverse events. However, behavioral symptoms are not always controllable with non-pharmacological intervention. The psychotropic class of medication more frequently prescribed for behavioral symptoms are atypical antipsychotics; among them, risperidone is the only one licensed for the treatment of aggression, in Europe but not in the USA. On that regard, the use of antipsychotic drugs should be limited, due to the increased risk of mortality, stroke, hallucination, and higher risk of relapse after discontinuation. Some new agents are under evaluation, such as pimavanserin and lumateperone. In this review, we are evaluating the current available pharmacological options to treat behavioral symptoms as well as the forthcoming new agents.